Frakturreduktion durch körperliches Training – Welches Training für wen? Eine evidenzbasierte Übersicht über Trainingsstrategien bei Osteoporose - von Stengel, Simon; Kemmler, Wolfgang (Osteologie, 2020)
Osteoporotic fractures are a highly relevant problem of our ageing society. The central goals of physical training are (1) 'fall reduction' and (2) 'increasing bone strength' as main determinants of osteoporotic fractures. Even though both paths should always be considered, bone density is the primary focus for 'younger' collectives, whereas falls should be adressed in older, functionally limited collectives at high risk for falls. From a training science perspective the design and implementation of effective anti-fracture training is complex and requires a combination of training contents and exercise parameters tailored to the training objective and target group. In order to increase bone strength, intensive osteogenic stimuli can be generated on bones via muscle traction and the resulting joint reaction forces or via axial loading leading to ground reaction forces. Accordingly, resistance exercise and weight-bearing high-impact exercises are the training contents of choice. Resistance exercise should be practiced intensity-based, whereby it should be progressively increased and periodized in accordance with the principles of competitive sports. Additionally power training can be considered for intensity progression to stimulate bone adaptation after an initial familiarization phase. High impact weight-bearing exercises, such as multidirectional jumps, are a second possibility to apply osteogenic stimuli to the bone. However, those exercises involve certain risks for injury and overload. Thus, the implementation of this training content should always be considered on a case by case basis. While resistance exercise has significant effects on lumbar and hip bone density similar to combined programs, combined programs are more effective than pure impact loads in terms of lumbar BMD. For persons that are not able or willing to perform conventional training whole-body vibration training is an effective and time saving alternative with impact on BMD and leg strength. Training that focuses on falls does not require high intensities and can easily be carried out with older functionally impaired people. In addition to balance training, functional training and, in particular, multimodal training programs including balance and resistance exercises have proven to be effective in reducing the number of falls or the fall risk. In view of the multimorbidity of many patients and a holistic development of the targeted components of motor performance, it is recommended that multifunctional programs combining resistance, coordination and endurance training are implemented, thus focusing on several health-oriented training goals.
CRIS-Team Scopus Importer:2020-09-11
Keywords: bone density; bone fracture; Osteoporosis; recommendation; training